Identification of the needs couples against prenatal class program in Badung Regency - Ni Komang Erny Astiti; Ni Made Dwi Purnamayanti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: Pregnancy causes changes in physical and psychological. Sometimes it causes a maturation crisis. The husband's support is expected to be optimal. So far, pregnancy education has focused on the mother, so the husband cannot carry out his role optimally.Objective: This study aims to identify the information needs of couples about the materials, methods, media, repetitions, and duration of couple prenatal class in Badung Regency.Methods: This research is a mixed-method explanatory sequential. This research was conducted in Badung Regency with 100 couples. Data analysis went through the stages of transcription, reduction, coding, categorization and finding themes. The results obtained six themes: subjects, functions, forms, awareness, quantity, and quality of health education. The next step is quantitative, the questionnaire contains the types of material needs, media, methods, duration and repetitions of health education needed by couples.The results of quantitative research were analyzed descriptive quantitatively..Result: This study consisted of 6 themes that were used as the basis for compiling a quantitative research. This research questionnaire consists of 30 items which include material, media, method, duration and repetition of health information needs about pregnancy, childbirth, postpartum and newborn which are assessed with a Likert scale.The findings revealed that the most common pregnant topics were fetal stimulation, danger indicators, and complaints, as well as how to deal with them. Pain management strategies, the role of the husband, and early breastfeeding initiation are the essential delivery materials. Danger indicators, breastfeeding issues, and managing and caring for postpartum are the most needed during the postpartum time. Bathing and caring for the umbilical cord, growth, development, and massage are the essential newborn care items. Interactive media, hybrid approaches, duration, and repetition of material adapted to the urgency and demands of couples are all desirable learning media.Conclusion: The needs of couples for health education in a couple of prenatal classes are very varied, including materials, media, methods, duration, and repetitions.